Pendidikan Agama Kristen Sebagai Sarana Pembentukan Karakter Dalam Konteks Multikulturalisme - Yuni Tobe; Jindry Tafuli; Semuel Linggi Topayung (Berkat : Jurnal Pendidikan Agama dan Katolik, 2024)
Christian Religious Education (CRE) plays a significant role as a means of character formation for students within the complex multicultural context of Indonesia. CRE not only emphasizes understanding Biblical teachings but also instills values such as love, tolerance, and moral responsibility, which are relevant to cultural and religious diversity. In a diverse society, character education through CRE aims to shape individuals who respect differences, are able to live harmoniously, and serve as "salt and light" in society. Through an inclusive and dialogical approach, CRE teaches students to appreciate diversity without losing their Christian identity. This study employs a literature review method to identify the challenges and opportunities in implementing CRE as a character-building tool in a multicultural society. The results show that a multicultural approach in CRE creates space for interfaith dialogue, helps prevent intolerance, and shapes a generation committed to values of peace and love. Thus, CRE not only plays a role in students' faith formation but also in building the tolerant character needed in a pluralistic society